A Rare Cause of Sleep-Disordered Breathing: ROHHAD Syndrome - Özcan, Gizem; Özsu, Elif; Şiklar, Zeynep; Çobanoğlu, Nazan (Frontiers in Pediatrics, 2020)
Rapid-onset obesity with hypoventilation, hypothalamic dysfunction, and autonomic dysregulation (ROHHAD) syndrome; is a rare but crucial disorder. Sleep-disordered breathing can occur at the beginning or after of obesity. A disease-specific test for diagnosis is not yet available. Neural crest tumors (ganglioneuroma, ganglioneuroblastoma) have been reported in 40% of patients. In our study, three patients diagnosed as having ROHHAD syndrome are presented from our hospital. In the evaluation of the hypothalamic functions of the patients, one of them had growth hormone deficiency and hyperprolactinemia; recurrent hypernatremia reflecting irregular water balance was detected in another. One of the patients had abnormal pupil reflex and heart rate irregularity while another had excessive sweating as autonomic dysfunction. One of the patients was diagnosed with paravertebral ganglioma accompanying ROHHAD syndrome. Non-invasive ventilation treatment was started in all patients because there was a sleep-disorder breathing clinic diagnosis. ROHHAD syndrome deserves a multidisciplinary team approach as it can affect more than one organ system. In these patients, should be sleep-disorder breathing determined early and appropriate treatment should be initiated immediately to reduce morbidity and mortality.